Paraneoplastic inflammation in myelodysplastic syndrome or bone marrow failure: case series with focus on 5‐azacytidine and literature review. (9th April 2014) - Frietsch, Jochen J.; Dornaus, Sebastian; Neumann, Thomas; Scholl, Sebastian; Schmidt, Volker; Kunert, Christa; Sayer, Herbert G.; Hochhaus, Andreas; La Rosée, Paul
Abstract Introduction Myelodysplastic syndrome (MDS) comprises a heterogeneous group of clonal disorders of haematopoietic stem cells, characterised by dysplastic haematopoiesis and dysregulated apoptosis resulting in various degrees of cytopenia, whereas canonical cytologic, cytogenetic and histopathologic findings guiding the diagnosis MDS are widely accepted, the MDS‐phenotype can be masked by coexisting/paraneoplastic immunologic disease. Autoimmune disorders have an estimated incidence of 10% among patients suffering from MDS and are causally related to increased morbidity and mortality, younger age at diagnosis and more complex genetics. Conversely, systemic inflammatory disorders may be an early manifestation of MDS, show good response to immunosuppressive therapy and frequently disappear during the course of specific haematologic therapy. Objective Monocentric report on clinical phenotypes found in MDS or bone marrow failure with paraneoplastic inflammatory disease. Methods Clinical case reports and systematic review about MDS pathophysiology and treatment. Results We report eight patients diagnosed with MDS or bone marrow failure, who presented with paraneoplastic autoimmune diseases. Six of eight patients were treated with the hypomethylating agent 5‐azacytidine, three of which achieved meaningful response with regard to inflammation control and haematologic recovery. Conclusions As paraneoplastic syndromes are often mistakenly diagnosed as idiopathic autoimmune disorders, we propose that coexistence of an underlying myelodysplastic syndrome should be considered early in the diagnostic work up. 5‐Azacytidine is effective in controlling paraneoplastic inflammation.